Effects of Demographic Change on Economic Growth: A Panel ARDL Approach for Selected OECD Countries - Ciftci, Hakki; Bilgin, Cevat; Bilgin, Handan Kaynar (Univ Economics-Prague, 2023)
The changing population dynamics have substantial impact on economy. This paper investigates the effects of demographic change on economic growth. The share of working age population, child dependency ratio, old-age dependency ratio and age dependency ratio are used as demographic variables. The effects of these variables on the gross domestic product per capita growth rate are examined for the OECD countries covering the period 1970-2021. Four different models are estimated by using panel ARDL estimation method. The findings derived from the estimated models point out that the old-age dependency ratio and age dependency ratio have negative effects on economic growth. On the other hand, the share of working age population has a positive effect on economic growth. These results suggest that demographic change causing an increase in the dependency ratio and a decrease in the share of working age population will have adverse impacts on economic performance in the long run.
Keywords: demographic change; economic growth; panel ARDL